Aggressive intraabdominal fibromatosis - Stojković Mirjana; Čolović Nataša; Micev Marijan; Radak Vladimir; Grubor Nikica; Čolović Radoje (Vojnosanitetski Pregled)
Background. Intraabdominal or mesenteric fibromatosis is a rare benign nonmetastatic neoplasm that appears as a sporadic lesion or in patients with familiar polyposis. Its evolution is unpredictable. About 10% of the cases show a very aggressive growth. Case report. We presented a 22-year-old woman in whom an aggressive intraabdominal fibromatosis had appeared during the first pregnancy as a well circumscribed ovoid tumor, involving the terminal ileum, the caecum, the ascending colon, the right kidney, the ureter, and the right common iliac artery. The tumor was excised with right colectomy, nephroureterectomy and resection of the involved artery using arterial reconstruction with graft interposition. Two years after the surgery the patient developed an inoperable tumor recurrence with a fatal outcome. Conclusion. In spite of a successful surgical excision during the original surgery intraabdominal or mesenteric fibromatosis might have an aggressive evolution leading to an inoperable tumor recurrency and a fatal outcome.